Gendered relationship between HIV stigma and HIV testing among men and women in Mozambique: a cross-sectional study to inform a stigma reduction and male-targeted HIV testing intervention. Issue 10 (7th October 2019) - Ha, Judy H; Van Lith, Lynn M; Mallalieu, Elizabeth C; Chidassicua, Jose; Pinho, Maria Dirce; Devos, Patrick; Wirtz, Andrea L
Abstract : Objectives: Increasing and sustaining engagement in HIV care for people living with HIV are critical to both individual therapeutic benefit and epidemic control. Men are less likely to test for HIV compared with women in sub-Saharan African countries, and ultimately have delayed entry to HIV care. Stigma is known to impede such engagement, placing an importance on understanding and addressing stigma to improve HIV testing and care outcomes. This study aimed to assess the gendered differences in the relationship between stigma and HIV testing. Design and setting: A cross-sectional, household probability survey was implemented between November and December 2016 in the Sofala province of Mozambique. Participants: Data were restricted to men and women participants who reported no prior diagnosis of HIV infection (N=2731). Measures: Measures of sociodemographic characteristics, stigma and past exposure to HIV interventions were included in gender-stratified logistic regression models to estimate the relationship between stigma and recent testing for HIV, as well as to identify other relevant correlates. Results: Significantly fewer men (38.3%) than women (47.6%; p<0.001) had recently tested for HIV. Men who reported previous engagement in community group discussions about HIV had an increased odds of testing in the past 12 months compared to those who had not participated (adjusted OR (aOR)=1.92; 95% CI 1.51 to 2.44). Concerns about stigma were not a commonly reported barrier to HIV testing; however, men who expressed anticipated individual HIV stigma had a 35% lower odds of recent HIV testing (aOR=0.65; 95% CI 0.44 to 0.96). This association was not observed among women. Conclusions: Men have lower uptake of HIV testing in Mozambique when compared to women. Even amidst the beneficial effects of HIV messaging, individual stigma is negatively associated with recent HIV testing among men. Intervention efforts that target the unique challenges and needs of men are essential in promoting men's engagement into the HIV care continuum in sub-Saharan Africa.